On the fractional integrodifferentiation of complex polynomials in L_0 - Kovalenko, L. G.; Storozhenko, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish Bernstein-type inequalities for the fractional integroderivatives of arbitrary algebraic polynomials in the space L_0.